Contemporary Muslim-Christian encounters developments, diversity and dialogues - Hedges, Paul (Bloomsbury Academic, 2017)
Contemporary Muslim-Christian Encounters: Developments, Diversity and Dialogues addresses the key issues in the present day global encounter between Christians and Muslims. Divided into two parts, the first examines theoretical issues and concerns which affect dialogue between the two traditions. The second part highlights case studies from around the world.